The Caloocan City Public Library an evaluation with implications for collection development - Dizon, Marie C. (1997)
The study was conducted to: 1) to ascertain the users' perceptions on the collection of the Caloocan City Public Library; 2) to determine the strengths and weaknesses of the collection; 3) to find out whether Caloocan City Public Library's staffing, physical facilities and collection meet the Minimum Standards for Public Libraries; and 4) to find out the programs of the library in upgrading the collection to meet the minimum requirements of the Standards for Public Libraries.